Emotional, physical and sexual abuse are associated with a heightened limbic response to cocaine cues. (22nd September 2016) - Regier, Paul S.; Monge, Zachary A.; Franklin, Teresa R.; Wetherill, Reagan R.; Teitelman, Anne; Jagannathan, Kanchana; Suh, Jesse J.; Wang, Ze; Young, Kimberly A.; Gawrysiak, Michael; Langleben, Daniel D.; Kampman, Kyle M.; et al.
Abstract: Drug‐reward cues trigger motivational circuitry, a response linked to drug‐seeking in animals and in humans. Adverse life events have been reported to increase sensitivity to drug rewards and to bolster drug reward signaling. Therefore, we hypothesized that cocaine‐dependent individuals with prior emotional, physical and sexual abuse might have a heightened mesolimbic brain response to cues for drug reward in a new brief‐cue probe. Cocaine‐dependent human individuals ( N  = 68) were stabilized in an inpatient setting and then completed an event‐related blood‐oxygen‐level dependent functional magnetic resonance imaging task featuring 500‐ms evocative (cocaine, sexual, aversive) and comparator (neutral) cues. Responses to three questions about emotional, physical and sexual abuse from the Addiction Severity Index were used to divide the patients into subgroups (history of Abuse [ n  = 40] versus No Abuse [ n  = 28]). When subjects were grouped by the historical presence or absence of emotional, physical or sexual abuse, the Abuse group showed a heightened midbrain, thalamic, caudate, and caudal orbitofrontal cortex response to cocaine cues; a similar result was found in other evocative cues, as well. These findings are the first reported for a 500‐ms cocaine‐cue probe, and they highlight the ability of very brief evocative cues to activate the brain's motivational circuitry. Although all participants had severe cocaine use disorders, individuals reporting prior abuse had a heightened mesolimbic response to evocative cues. To our knowledge, this is the first study in humans linking a history of abuse to a brain vulnerability (heightened mesolimbic response to drug cues) previously shown to contribute to drug‐seeking. Abstract : Even though all participants had severe cocaine disorders, individuals with a history of emotional, physical, and/or sexual abuse exhibited a heightened mesolimbic response to cocaine cues compared with those without a history of abuse.